Internalization of character education values in the creative process of lontar transcripts of STKIP agama Hindu Amlapura students - Jatiyasa, I Wayan; Apriani, Ni Wayan; Paramanandani, Ni Kadek Ayu (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
The development of the times is so fast that it affects various things including student character. The importance of integrated character education in various lessons is no exception in the Lontar Transcript course in the Balinese Language Education Study Program. The integration of character education provides strengthening for students who will later become teachers so that they can provide strong character education values for their students. This study aims to analyze the character education values integrated in the lontar transcription of STKIP Hinduism Amlapura students. This research is a qualitative research, with the locus of research at STKIP Agama Hindu Amlapura. The type of data uses qualitative and quantitative data, while the data source uses primary and secondary data sources. Data collection methods use participatory observation methods and questionnaires. Data analysis using descriptive statistics. Based on the results of the study, it shows that students of STKIP Agama Hindu Amlapura internalize 17 character education values in the process of creativity of lontar transcripts, namely hard work, independence, religion, curiosity, responsibility, discipline, creativity, love for the country, honesty, love to read, respect for achievement, tolerance, democratic, peace-loving, communicative, environmental care, and social care. The process of internalizing character education values in STKIP Agama Hindu Amlapura students' lontar transcripts, including receiving, responding, selecting, internalizing, and applying values.